PENGENALAN KEGIATAN EDUPRENEUR BAGI ANAK USIA DINI DI RA AL-MUSLIMUN NURUL ISLAM PALANGKA RAYA - Aghnaita; Muzakki; Afifah, Neela; Ervina; Ma’rifah, Nor; Isnawati; Rahmi, Anida (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
This community service is motivated by the importance of introducing learning to children, especially in introducing edupreneur activities. Based on this, it is necessary to provide an introduction to edupreneur activities in order to enable children to have entrepreneurial education through bazaar activities. The aim of this community service is so that children can get to know about educational activities that have been carried out, namely bazaar activities. Through these activities it can also teach children about transactions when selling, namely the existence of sellers and buyers. The targets for community service participants are children aged 5-6 years who are at RA Al-Muslimun Nurul Islam Palangka Raya and students of the Early Childhood Islamic Education Study Program, Faculty of Tarbiyah and Teacher Training, IAIN Palangka Raya, who are also actively involved in this activity. . The results of this community service show that the children are very enthusiastic about taking part in the bazaar activities that have been carried out at school and are enthusiastic. The hope is that through the introduction of edupreneur activities carried out in early childhood, it will be able to stimulate children's character education, introduce children to entrepreneurship education, and increase children's experience because they have carried out edupreneur activities, namely through bazaar activities. So that the aim of the introduction will be achieved optimally.